Isolation of Human Photoreceptor Precursors via a Cell Surface Marker Panel from Stem Cell‐Derived Retinal Organoids and Fetal Retinae. (1st February 2018) - Lakowski, Jörn; Welby, Emily; Budinger, Dimitri; Di Marco, Fabiana; Di Foggia, Valentina; Bainbridge, James W.B.; Wallace, Kyle; Gamm, David M.; Ali, Robin R.; Sowden, Jane C.
Abstract : Loss of photoreceptor cells due to retinal degeneration is one of the main causes of blindness in the developed world. Although there is currently no effective treatment, cell replacement therapy using stem‐cell‐derived photoreceptor cells may be a feasible future treatment option. In order to ensure safety and efficacy of this approach, robust cell isolation and purification protocols must be developed. To this end, we previously developed a biomarker panel for the isolation of mouse photoreceptor precursors from the developing mouse retina and mouse embryonic stem cell cultures. In the current study we applied this approach to the human pluripotent stem cell (hPSC) system, and identified novel biomarker combinations that can be leveraged for the isolation of human photoreceptors. Human retinal samples and hPSC‐derived retinal organoid cultures were screened against 242 human monoclonal antibodies using a high through‐put flow cytometry approach. We identified 46 biomarkers with significant expression levels in the human retina and hPSC differentiation cultures. Human retinal cell samples, either from fetal tissue or derived from embryonic and induced pluripotent stem cell cultures, were fluorescence‐activated cell sorted (FACS) using selected candidate biomarkers that showed expression in discrete cell populations. Enrichment for photoreceptors and exclusion of mitotically active cells was demonstrated by immunocytochemical analysis with photoreceptor‐specific antibodies and Ki‐67. We established a biomarker combination, which enables the robust purification of viable human photoreceptors from both human retinae and hPSC‐derived organoid cultures. Stem Cells 2018;36:709–722 Abstract : Cell surface (cluster of differentiation markers; CD) markers expressed on human retinal cells were identified using BD lyoplate antibody screening panels. Fluorescence‐activated cell sorting (FACS) and CD marker antibodies were used to purify photoreceptor cells from dissociated human pluripotent stem cell (hPSC)‐derived retinal organoids and fetal retinae. Purified human photoreceptor cells are useful for cell therapy and study of retinal disease.